THE TARGETS OF MONETARY POLICY IN RUSSIA - G.A. KUDINOVA (Advanced Engineering Research, 2007)
The Central bank conducts a monetary policy. The targets of monetary policy are an unemployment, inflation, economic growth, stability financial markets. The main problem of monetary policy it is impossible to control all this targets. The Bank of Russia realizes a monetary target to. The main target of Bank of Russia since 1992 year is level of inflation.